Nickel: A tale of two cities - Richard Schodde; Pietro Guj (Geosystems and Geoenvironment)
Asides from subsea manganese nodules, there are essentially three main sources of nickel (Ni) supply: newly mined (1) magmatic Ni sulfide ore, (2) Ni laterites (limonitic and saprolitic) and (3) new and old End-of-life (EoL) recycled stainless steel scrap, mostly melted to produce stainless steel of similar grade. Traditionally Ni sulfide ore has been refined into high-purity, LME-deliverable, Class 1 products, such as Ni briquettes and powder for a range of specialised applications, besides stainless steel, including chemical EV battery precursors. By contrast, Ni laterites have been in the past the primary source of lower-purity, Class 2 products, such as ferronickel and nickel pig iron (NPI) as feed for stainless steel production. Processing of Ni laterites using high pressure acid leaching (HPAL) has generally proven to be technically complex and often the source of financial problems. This, however, has changed starting with a daring but successful gamble on the side of Ni-laterite-rich Indonesia that, in an endeavour to attract investment in downstream processing, in 2014 introduced a ban on the exportation of Ni ore, giving local miners 5 years to establish their processing facilities. Initially the Indonesian Ni industry languished, much to the benefit of Ni producers elsewhere, until China entered the scene financing downstream processing of Ni laterites at an unprecedented scale and more recently introducing innovative improvements to the HPAL process to a level that makes production of refined Ni products from laterites, not only possible, but competitive with traditional Ni sulfide sources. This has had a devastating effect on Ni sulfide mines, with many suspending and others reducing production. There is no doubt that economies of scale, metallurgical innovation, and massive, low-cost Chinese funding are behind this success, even though the Ni sulfide sector claims that central to it is a somewhat accommodating attitude on the side of the Indonesian environmental authorities. The attempt on the side of Ni sulfide miners to differentiate themselves as ‘clean’ Ni producers deserving a price premium did not get traction, but concerns regarding the environment, the impact on the affected communities, and the long-term sustainability of the lateritic Ni resources appear to be emerging as serious political issues in Indonesia. The paper analyses the size, composition, and geographical distribution of the current world Ni resources, their growth, and their capacity to satisfy the medium-term increase in demand due to the transition to clean energy despite diminishing exploration discoveries. It also speculates on how long the current laterite dominance of the Ni market may persist before the pendulum may swing back to Ni sulfides. Despite rising environmental pressure, there appears to be a reasonable chance that current and foreseeable Ni resources may prove adequate to satisfy rising demand in the short to medium term. By contrast, modelling indicates that there will be inevitable severe pressure on Ni supply in the next century and beyond. Opinions, however, differ as to the degree to which these will represent a treat to human civilisation. These range from catastrophic consequences to greater faith in human ingenuity enabling a slow, progressive process of adaptation to use primary Ni more sparingly as it becomes increasingly scarce and unbearably expensive, because of the exponential increase in the cost of metallurgy and disposal of mine waste inherent in extracting Ni from progressively lower grade and deeper deposits. The push will be to lower Ni-intensity, developing material technology substitutes for it in consumptive applications, and by promoting innovative manufacturing with a clear focus on re-cycling, to achieve the highest possible level of circularity. Hopefully, a balance may eventually be reached, not without some significant sacrifices in terms of living standards, whereby Ni demand will be reduced to a sustainable level that can be satisfied indefinitely primarily by recycled Ni complemented by limited quantities of primary Ni.